Cognitive Enhancement as a Pharmacotherapy Target for Stimulant Addiction - Sofuoglu, Mehmet (2010)
BACKGROUND: No medications have been proven to be effective for cocaine and methamphetamine addiction. Attenuation of drug reward has been the main strategy for medications development, but this approach has not led to effective treatments. Thus, there is a need to identify novel treatment targets in addition to the brain reward system. AIM: To propose a novel treatment strategy for stimulant addiction that will focus on medications enhancing cognitive function and attenuating drug reward. METHODS: Preclinical and clinical literature on potential use of cognitive enhancers for stimulant addiction pharmacotherapy was reviewed. RESULTS AND CONCLUSIONS: Cocaine and methamphetamine users show significant cognitive impairments, especially in attention, working memory and response inhibition functions. The cognitive impairments seem to be predictive of poor treatment retention and outcome. Medications targeting acetylcholine (Ach) and norepinephrine (NE) are particularly well-suited for enhancing cognitive function in stimulant users. Many cholinergic and noradrenergic medications are on the market, have a good safety profile, and low abuse potential. These include galantamine, donepezil, and rivastigmine (cholinesterase inhibitors), varenicline (partial nicotine agonist), guanfacine (alpha(2)-adrenergic agonist), and atomoxetine (norepinephrine transporter inhibitor). Future clinical studies optimally designed to measure cognitive function as well as drug use behavior would be needed to test the efficacy of these cognitive enhancers for stimulant addiction.